What Factors Affect The Integrity Of Financial Statements? - Octavian Imon, Kevin; Santi, Fitriana; Fitriyani, Yuniar (University of Merdeka Malang, 2025)
This research aims to analyze the effect of managerial ownership, leverage, and company size on the integrity of financial statements in non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) in 2024. The data used is secondary data obtained from the company’s annual financial statements published on the official website of the Indonesia Stock Exchange (IDX) in 2024. Data collection techniques were conducted through documentation, and the data were analyzed using multiple linear regression analysisi. The results of the study indicate that managerial ownership and leverage have a significant effect on financial statement integrity. Meanwhile, company size does not show a significant effect on the integrity of financial statements. Simultaneously, all independent variables in this research were found to have a significant effect on the integrity of financial statements. Managerial ownership, leverage, and company size account for 40,5% of the influence, while the remaining 59,5% is influenced by factors outside the variables in this study.